Confined collections: Prison heritage and its objects (in Brazil and Portugal at the present time) Collections confinées: le patrimoine pénitentiaire et ses objets (au Brésil et au Portugal aujourd'hui) Acervos confinados: o património prisional e os seus objetos (no Brasil e em Portugal no tempo presente) - Borges V.T.* (2021)
© 2021 Centro de Estudos Sociais da Universidade de Coimbra. All rights reserved.This paper deals with prison memory spaces located in Brazil and Portugal. The focus is on paintings and drawings, created by prisoners and ex -prisoners, understood as places of knowledge/power which not only contain visual information about the activities performed within the confinement space but also make it possible to look into the paths and choices that shape prison heritage. These collections are understood here as visual objects producing and receiving sense, and endowed with agency, vectors that allow us to think about the relationships established from them as potentialities enabling discussion of the notion of prison heritage. I will dwell on other supports, such as murals and graphics, examining their weaknesses and absences.